Research and Design of Varian Accelerator Quality Management Monitoring System Based on Log Files - Jinhong YAO; Yan JIN; Xinyu ZHAO (Zhongguo yiliao qixie zazhi)
In order to track the running status of the accelerator in real time, discover potential problems in time, reduce the failure rate, and ensure the safety of radiotherapy patients, a linear accelerator quality management monitoring system is designed based on log files. The system adopts B/S architecture, with the server written in Python3.7 language, and is built based on Django2.2.7 framework. The system uses Python3.7 and Pylinac packages to analyze the log files of each plan, obtaining the planned beam quantity, flux gamma pass rate, and position information of multileaf collimator, etc., to realize the quality monitoring of medical linear accelerator, and customize the development of accelerator spare parts and maintenance management modules. According to statistics, after the establishment of the quality management monitoring system, the accelerator has achieved a 16% reduction in failure rate and a 30% reduction in the downtime rate, which ensures its stable operation in clinical settings.